A new correction method of the blockage on a rectangular antenna based on numerical simulation. (2016) - Du, Qiang; Wang, Fuzhi; Du, Fuyin
In this paper, the blockage effects on a rectangular antenna are investigated through numerical simulation, and a correction method for the wind load coefficients is presented. In terms of the separation pressure measured by the wind tunnel test and the law of separation pressure with blockages achieved from the numerical simulation, we derive a relationship for base pressure coefficient of the rectangular antenna with various blockages. Adopting the formula based on the potential flow theory, the drag coefficient without blockage can be obtained. Using the base pressure coefficient to re-normalise the pressure coefficient, the characteristic that the re-normalised pressure coefficient the antenna is independent of the blockage ratio is verified. Furthermore, the pressure distributions on the rectangular antenna without blockage are obtained by the re-normalised pressure coefficient. The corrected results show that the blockage effect on pressure and drag force on the rectangular antenna both are removed effectively.